Penentuan Ambang Curah Hujan untuk Memprediksi Kejadian Longsor - Rokhmat Hidayat; Avidah Amalia Zahro (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
The mayority of landslide occur due to high rainfall in certain time in areas that have geological potential landslides. Therefore, it is necessary to conduct a research on rainfall characteristics that trigger landslides. So that, it can be used to establish the relationship between rainfall and predicted landslides. This research is aimed to analyze and determine the daily and 3 days rainfall thresholds used for landslides early warning system (LEWS). The case study is placed in both very high risks and high area landslide areas, based on the ground motion maps of the Geological Agency. The analysis was done based on landslide event data from BNPB, as well as TRMM (Tropical Rainfall Measuring Mission) and ECMWF (The European Center for Medium-Range Weather Forecasts) rainfall data. Identification of the rain trigger values from the TRMM rain data was done after collecting landslide incidents at various locations.. The results show that the rainfall threshold values are 61 mm per day and 91 mm per 3 days Keywords: Rainfall treshold,landslide prediction, TRMM, ECMWF